Urinary exosomes: a promising biomarker of drug-induced nephrotoxicity - Zhou, Zunzhen; Zhang, Dailiang; Wang, Yongjing; Liu, Chongzhi; Wang, Limei; Yuan, Yi; Xu, Xiaodan; Jiang, Yuan (Frontiers in Medicine, 2023)
Drug-induced nephrotoxicity (DIN) is a big concern for clinical medication, but the clinical use of certain nephrotoxic drugs is still inevitable. Current testing methods make it hard to detect early renal injury accurately. In addition to understanding the pathogenesis and risk factors of drug-induced nephrotoxicity, it is crucial to identify specific renal injury biomarkers for early detection of DIN. Urine is an ideal sample source for biomarkers related to kidney disease, and urinary exosomes have great potential as biomarkers for predicting DIN, which has attracted the attention of many scholars. In the present paper, we will first introduce the mechanism of DIN and the biogenesis of urinary exosomes. Finally, we will discuss the changes in urinary exosomes in DIN and compare them with other predictive indicators to enrich and boost the development of biomarkers of DIN.